Pengaruh Physical Evidence Dan Perceived Value Terhadap Revisit Intention Dengan Kepuasan Pengunjung Sebagai Variabel Intervening - Syofiatul Safitri; Sofie Amalia Ul Umma (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Along with the increasing public interest in fun recreational activities such as water parks, the tourism sector has grown rapidly in recent years. This study examines the effect of physical evidence and perceived value on revisit intention through visitor satisfaction as an intervening variable for visitors to Labersa Waterpark Riau Fantasi. This research was conducted using quantitative research methods. The sampling technique used was Accidental Sampling with a sample size of 98 respondents. The data obtained is then processed using SmartPLS 4.0 software. The results of this research are : (1) physical evidence has a significant effect on revisit intention, (2) perceived value has a significant effect on revisit intention, (3) physical evidence has a significant effect on visitor satisfaction, (4) perceived value has a significant effect on visitor satisfaction, (5) visitor satisfaction has a significant effect on revisit intention, (6) visitor satisfaction is able to mediate the effect of physical evidence on revisit intention, (7) visitor satisfaction is able to mediate the effect of perceived value on revisit intention.